استعمال القضايا اللغوية عند الزمخشري للدفاع عن عقيدته الاعتزالية: عرض ونقد في مسألة رؤية الله تعالى - Syed Abdul Rahman, Syed Mohammad Hilmi; Sayyed Ali al-Mahdaly, Sayyed Abdul Hamid (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
Ru’yah Allah has become a popular issues which continuous extensively debated in the science of theology (Kalam). This article discussed Ru’yah Allah from al-Zamakhshari, a Mu`tazilite mufassir perspective who defended his opinion on this issue. The discussion refered to the language aspect of al-Nahw and al-Balaghah. It examined the thought of al-Zamakhshari in the interpretation of the Qur’an, and the study found that in the Qur’an there were three words related with Ru’yah: al-Idrak, al-Ru’yah and al-Nazar. In this issue al-Zamakhshari used a method of returning the al-Mutashabihat verses to the al-Muhkamat. He then, concluded in line with Mu`tazilite’s absolute opinion that al-Ru’yah will never be achieved in the Hereafter,. However, this opinion was contrary to the opinion of al-Salaf al-Salih, which did not allow the anthropomorphism between al-Khaliq and al-Makhluq as accepted by the Mu'tazilites. Mu'tazilites considered that to enable something to be seen, it must be in a certain space or position, and since God is not in a specific space and position, thus God cannot be seen. This stance was refuted by al-Salaf al-Salih by arguing that Allah cannot be compared at all with His creation because there is nothing comparable to Him. Based on the opinion of al-Zamakhshari on al-Ru’yah, this article then led a discussion on the aspects of al-Nahw and al-Lughah in order to understand the probability of his selction of meaning in his Qur’anic verses interpretation had been influenced by his school of thought. This study of al-Zamakhshari was very important especially because al-Kashshaf was considered among the most important reference exegesis that determine a more accurate opinion on issues related to al-Balaghah.